2018
DOI: 10.1007/s00330-018-5315-4
|View full text |Cite
|
Sign up to set email alerts
|

Helical CT with variable target noise levels for dose reduction in chest, abdomen and pelvis CT

Abstract: • Low dose chest and standard abdomen CTs can be combined. • Variable SD CT scanning allows for radiation dose reduction. • Variable SD CT scanning maintains image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Supraventricular arrhythmias, such as atrial fibrillation, generally have a long history, significant myocardial fibrosis, more complications, high risk of stroke with drug therapy, poor efficacy, and arrhythmogenic effects with the long-term application of antiarrhythmic drugs in such patients. Therefore, there is much interest in the clinical effectiveness and safety of transcatheter ablation for the treatment of AF [ 19 ]. Current studies suggest that most cases of paroxysmal AF are triggered or driven by the extracardiac abnormal potential sites and the pulmonary veins are the most common sites of origin for such arrhythmias that often cause paroxysmal AF.…”
Section: Related Workmentioning
confidence: 99%
“…Supraventricular arrhythmias, such as atrial fibrillation, generally have a long history, significant myocardial fibrosis, more complications, high risk of stroke with drug therapy, poor efficacy, and arrhythmogenic effects with the long-term application of antiarrhythmic drugs in such patients. Therefore, there is much interest in the clinical effectiveness and safety of transcatheter ablation for the treatment of AF [ 19 ]. Current studies suggest that most cases of paroxysmal AF are triggered or driven by the extracardiac abnormal potential sites and the pulmonary veins are the most common sites of origin for such arrhythmias that often cause paroxysmal AF.…”
Section: Related Workmentioning
confidence: 99%
“…Multiple phase contrast enhanced abdominal CT is an inestimable diagnostic tool for patients with kinds of chronic diseases, especially for tumors [1,2]. However, concerns remain about the potential risks of ionizing radiation, particularly for populations that may require serial CT examinations [3][4][5]. Previous studies have reported that the low tube-voltage technique (e.g., 80 kV) could e ciently reduce the radiation dose and increase the contrast enhancement of vascular and parenchymal structures in abdominal contrast enhanced CT[6].…”
Section: Introductionmentioning
confidence: 99%